Concepts and essential features of environmental land use - Hetmanchyk, I.; Chumachenko, O.; Kolhanova, I. (Land Management, Cadastre and Land Monitoring, 2021)
Among the most important problems of socio-economic development of society, special importance belongs to the effective use of land and resources, on which depends the economic, social, environmental security of the state and living standards. Negative trends observed in the process of land use require new organizational and legal approaches to regulating land use and creating economic incentives for rational use and protection of land in Ukraine. In this article the concept and functioning of "land use" as a natural, legal and economic category is considered. The essence and formation of an integrated system of environmental land use, which includes: part of a single land fund (land, land and rights to them), provided by the state or acquired or leased by a separate owner or user, the boundaries of which are determined on the ground; land object of law, object of economic, ecological, town-planning, agricultural and other land relations, for which the land user is issued a document certifying the right to land with certain boundaries, area, composition of lands, property objects and, if necessary, with geodetic coordinates of boundary signs defined in nature and the process of human (society) use of the integrated potential of the natural territory are revealed. The concept and essence of "land-territorial resource" are studied. Keywords: land, land, land use, land management, agricultural and environmental land use, territory.